Developing Translation and Interpretation Skills: An Analysis of Students’ Linguistic Needs - Elmahdi, Omer Elsheikh Hago; Mohamad, Hanan Mahgoub Hamed (Arts for Linguistic & Literary Studies, 2024)
This study aimed to investigate the views of final year students of Department Languages ​​and Translation at Taibah University regarding the skills required for professional success through the needs analysis approach. This study investigated the perspectives of 100 final year translation and interpretation students at Taibah University in Saudi Arabia regarding the professional competencies needed for career success. A 21-item Likert-scale needs analysis questionnaire captured students' views. The results showed that students showed high agreement on the skill importance (M=4.55). The results showed that students at high level considered the sufficiently of current translation approach (M=3.72). Students also highly agreed on the existed substantial barriers with 3.78. Finally, students reported with very high rate (4.2) about the necessity of making changing in the curriculum practices. The study recommends aligning efforts with competency priorities reported by students promises continuously optimized outcomes. Recurring assessment input as stakeholders informs responsive planning per evolving needs amidst global demands. This methodology elevates student perspectives to guide curriculum improvements towards employer-relevant skill-building.